PENGARUH STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN PADA HOTEL PLAZA KUBRA KENDARI - Djauhar, Asri; Baso, Nasir Andi; Subhan, Subhan (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
This study aims to determine the effect of work stress on employee performance at the Hotel Plaza Kubra Kendari. To achieve this goal, qualitative and quantitative data are used, data collection techniques by observation, interviewes and literature study are used.The population in this study were all employees of the Hotel Plaza Kubra Kendari, totaling 25 people. Sampling using non-probability sampling technique or census method. The data collection instrument used a questionnaire with a likert scale, each of which had been tested and had met the validity and reliability requirements. Data analysis using simple linear regression and using hypothesis testing, namely partial t test and determination R test.Based on the results of simple linear regression analysis, it shows that there is a positive and significant effect between work stress on employee performance at the Hotel Plaza Kubra Kendari with a tcount 6,205 > ttable 2,069 with a significance value of 0,00 < 0,05. So that the proposed hypothesis can be accepted. Based on this, it shows that work stress has a positive and significant effect on employee work performance at the Hotel Plaza Kubra Kendari.